Cloning of Partial β-Mannanase Gene from Indonesia Marine Bacteria Bacillus Subtilis LBF-005 - Yopi yopi; Nanik Rahmani; Maghfirotul Amaniyah; Apridah Cameliawati Djohan (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2017)
The strain LBF-005 from marine bacteria have already isolated and screened for mannanase degrading enzyme in submerged fermentation process. This strain was further identified by using 16S rRNA showed that bacterium is belong to Bacillus subtilis that could produce mannanase with activity around 9.5 U/mL. The optimum pH and temperature for the activity of crude enzyme for mannanase was 6.0 and 50 oC. Cloning of mannanase gene from B. subtilis was conducted using six primers set designed based on the homology analysis conserve region several mannanase from bacteria (Bacillus sp.) glycosyl hydrolase (GH) family 26. Optimization of PCR conditions was performed by gradient PCR to obtained PCR product of b-mannanase gene. The PCR product was obtained by third primer combination and was estimated to be around 972-bp. Analysis of the nucleotide sequence showed that sequences has similarity with mananase gene from other Bacillus sp., such as the B. subtilis strain WLY-12, B. subtilis strain WL-8, B. subtilis strain CICC 10260, B.subtilis strain CD-25, B.subtilis strain G1, and Bacillus sp. SWU60 were about 98%, 98%, 98%, 98%, 97% and 95%, respectively. The next research will to obtain a whole gene encoding β-mannanase by using in vitro cloning method, characterization of recombinant mannanase and application this enzyme for mannooligosaccharides production.